Roles of Psychological Distress and Social Support in the Relationship Between Childhood Maltreatment and Perceived Needs for Mental Health Care - Gao, Tingting (Journal of interpersonal violence, 2022)
Childhood maltreatment is a major public health issue worldwide. It increases a range of health-risk behaviors, psychological and physical problems, which are associated with an increased need for mental health services in adulthood. Identification of mediating factors in the relationship between maltreatment and seeking mental health care may help attenuate the negative consequences of childhood maltreatment and promote more appropriate treatment. This study aims to examine whether the relationship between childhood maltreatment and perceived need for mental health care is mediated by psychological distress and/or moderated by social support. Data from the Canadian Community Health Survey-Mental Health 2012 are analyzed. A total of 8,993 participants, who had complete information on childhood maltreatment and diagnoses of mental disorders or psychological distress, are included in this study. Structural equation modeling and the PROCESS macro were used to identify relationships among childhood maltreatment, perceived needs for mental health care, and psychological distress. Hierarchical linear regression was then used to verify the moderated mediation model. We found that psychological distress partially mediated the effect of childhood maltreatment on perceived needs for mental health care in adulthood. Social support played an important role in terms of moderating the relationship between maltreatment and perceived needs for care. For those with a history of childhood maltreatment, those who perceived a low level of social support were more likely to have higher levels of psychological distress and perceived need for mental health care. This is the first study to identify the separate and combined roles of psychological distress and social support in the relationship between childhood maltreatment and perceived need for mental health care. Selective prevention strategies should focus on social support to improve mental health services among people with a history of childhood maltreatment.